Finite Element Analysis of Horizontal Bearing Capacity for the Composite Diaphragm Wall Anchor Foundation - Qian Yin; Leyong Wei; Xiaojuan Li; Weiming Gong; Xueying Yang; Guoliang Dai; Shunkai Peng (Buildings)
A composite diaphragm wall anchor foundation (CDWAF) is a novel type of anchor foundation, but research on its bearing performance remains limited. In this study, the horizontal bearing characteristics of a CDWAF and the interaction mechanism between the foundation and surrounding soil using finite element analysis were investigated. The foundation’s displacement behavior under external loads, the distribution of resistance from various soil components, and the failure mechanisms of the foundation were also studied. The results reveal that under external loads, the CDWAF experiences both rigid-body translation and rotational displacement, with the rotation center shifting dynamically to the upper right with the increase in load. At the failure state, a passive failure wedge forms on the outer side of the front wall of the foundation due to soil compression, while an active failure wedge develops on the outer side of the back wall, and both the displacement and rotation of the foundation increase nonlinearly with the applied load. As the load increases, the passive earth pressure on the front wall’s outer side rises, while the active earth pressure on the back wall’s outer side decreases. The distribution of soil resistance and side friction resistance of the CDWAF with depth is influenced by the critical depth, which increases with the load. The soil resistance at the bottom of the foundation shows an overall increase in the direction of the applied load, peaking at the bottom of the front wall. The plastic zone in the surrounding soil progressively develops, starting at the base and the outer sides of the front and back walls. Notably, the embedded end of the CDWAF significantly reduces the plastic failure at the bottom of the foundation. In comparison with traditional gravity caissons, the embedded end and internal compartments of the CDWAF effectively enhance its horizontal bearing capacity by 30% and 6%, respectively. At the same time, the mechanism of soil resistance is changed with the foundation type. The load-sharing ability of the cabinet foundation reaches 23% at the bottom and 45% outside the front and rear walls, respectively, while the load-sharing ratio of the composite diaphragm wall anchorage foundation is transferred from the base to the outer sides of the front and back walls, which is 5% and 58%, respectively. These findings contribute valuable insights to the design and application of underground diaphragm wall foundations in anchor foundation engineering.